Номінування адресата мовлення у «Приватному листуванні ХVІІІ ст.» - Павленко, Лариса; Pavlenko, Larysa (Східноєвропейський національний університет імені Лесі Українки, 2016)
Пропонована розвідка є спробою описати мовно-стильові особливості такого функціонального різновиду староукраїнської літературної мови, як приватний епістолярій. Хронологія аналізованого матеріалу – ХVІІІ ст. – час, коли остаточно виформовувалися основні ознаки літературної мови української нації. «Приватне листування ХVІІІ ст.» – історичне джерело, дослідження якого дозволяє обʼєктивно пізнати шляхи становлення і розвитку норм української мови, зʼясувати співвідношення книжної і народнорозмовної стихій. Епістолярій ХVІІІ ст. – конгломерат різних за походженням і за стильовими особливостями мовних елементів, серед яких важливе місце посідають номінації адресата мовлення, які були обовʼязковими клішованими компонентами памʼяток цього стилю. Адресат мовлення міг бути позначений різними способами: від окремих слів до розгорнутих словосполучень. This research is an attempt to describe the linguistic and stylistic peculiarities of such an old Ukrainian literary language functional variety, as private epistolary. Chronology of the analyzed material (XVIII-th century) covers the time, when the basic features of the literary language of the Ukrainian nation had been already firmly established. Colloquial version of Ukrainian national language appeared to be an important basis for the formation of the literary language. The author emphasizes that it is a fundamental factor, which stimulates the study of the Ukrainian language annals, approximated to the spoken elements. «Private correspondence of the eighteenth century» is an important historical source, the study of which allows to examine objectively the ways of formation and development of the Ukrainian language standards, and explore the relationship of the bookish and colloquial elements. Epistolary of XVIII-th century is analyzed in the article as a conglomerate of language elements, different by their origin and stylistic features, among which a special place belongs to the nominations of the addressee, namely the obligatory clichéd components used in the specified style of language material. The analysis allows to conclude that an addressee could be referred to in different ways, from single words to extended word combinations.
Nomination of the Addressee in the «Private Correspondence of the Eighteenth Century»
Keywords: діахронічний аспект; епістолярний стиль; номінація; адресат мовлення; diachronic aspect; epistolary style; nomination; addressee